Effects of defect creation and passivation on graphite friction under ultra-high vacuum conditions - Zhou, Xiang; He, Wenjie; Liu, Changtao; Zhang, Honglin; Sun, Junhui; Wang, Wen (Carbon (New York), 2024)
Graphite holds significant promise as a solid lubricating material for machine operation in ambient conditions. However, the intricacies of its mechanism remain a subject of debate at the nanoscale. In this study, atomic force microscopy (AFM) experiments conducted in ultrahigh vacuum (UHV) conditions provide direct evidence that the adsorption of water molecules significantly compromises friction performance, both on the basal plane and across step edges. This challenges the longstanding belief that the poor lubricating properties of graphite in a vacuum result from the desorption of water molecules. Moreover, the experimental findings put forth a compelling bond passivation hypothesis for graphite lubrication in ambient conditions. The process involves the introduction of defects with dangling bonds on graphite through annealing highly oriented pyrolytic graphite (HOPG) at elevated temperatures (≥773 K) in UHV conditions. Subsequently, these dangling bonds are gradually passivated by a small amount of residue atoms or molecules. Consequently, the continuously monitored friction force exhibits an exponential decrease over time following annealing. This study advances a molecular level understanding of low lubrication mechanism for graphite. [Display omitted]